Reduction over Condensation of Carbonyl Compounds Through a Transient Hemiaminal Intermediate Using Hydrazine - Yanez-Sanchez, M; Luhr-Sierra, S (American Chemical Society, 2020)
Reduction of carbonyl moieties to the corresponding alcohol using simply hydrazine hydrate has been considerably unfeasible until now due to the well-known condensation reaction. However, herein, we report that using an excess of 20-fold equivalents, the reduction proceeds in excellent yields. 1H NMR study of the reaction and density functional theory (DFT) calculations indicate that the final fate of the hemiaminal intermediate is crucial to obtain the alcohol or the hydrazone. Copyright © 2020 American Chemical Society.